2012
DOI: 10.1074/jbc.m111.301549
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Interaction between Annexin A2 and Keratin 17

Abstract: Background: Expression of EGFR, K17, and AnxA2 are correlated in cancer settings. Results: AnxA2 and K17 physically interact and undergo reciprocal regulation controlled in part by EGFR signaling. Conclusion: K17 serves as a regulator of the signaling pathway involving AnxA2, whereas AnxA2 regulates K17 stability. Significance: This study demonstrates a novel interaction and reciprocal regulation between AnxA2 and K17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 45 publications
3
28
0
Order By: Relevance
“…In the present study, we demonstrated that EGFR activation is a negative regulator of K8/K18 tyrosine phosphorylation in the insoluble compartment. Because K8 phosphorylation at Tyr-267 decreases K8 solubility, our findings align with a recent study showing that longer EGFR activation (1 h) increases the levels of soluble K17 (38).…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, we demonstrated that EGFR activation is a negative regulator of K8/K18 tyrosine phosphorylation in the insoluble compartment. Because K8 phosphorylation at Tyr-267 decreases K8 solubility, our findings align with a recent study showing that longer EGFR activation (1 h) increases the levels of soluble K17 (38).…”
Section: Discussionsupporting
confidence: 81%
“…Keratins are also involved in protein synthesis and epithelial cell growth (Kim et al, 2006), signaling (Alam et al, 2011), organelle transport (Planko et al, 2007), and cell mobility and proliferation (Chung et al, 2012). There are 54 genes that encode type I (acidic) and type II (basic) keratins, which form heterodimers and show tissue-specific expression (Flitney et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An NS shRNA has also been described previously (Chung et al, 2012). A SCR shRNA was designed by scrambling the KRT17 targeting sequence at position 387 (Table 2) and cloned in pSuper.…”
Section: Plasmids and Sirnasmentioning
confidence: 99%
“…) for a Krt17 null allele were isolated and cultured as described previously (Chung et al, 2012 ) for the Krt17 allele were isolated by mincing ears into fine pieces and subjecting them to 0.25% Trypsin overnight. After vigorous vortexing, free keratinocytes were isolated as described previously (Chung et al, 2012) and cultured in Cnt-57 medium (CELLnTEC) before harvesting.…”
Section: Rna Ipmentioning
confidence: 99%
See 1 more Smart Citation